2014
DOI: 10.1556/oh.2014.29795
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic aspects of celiac disease

Abstract: A coeliakia genetikai háttere már évtizedek óta intenzív kutatás tárgya. Ennek ellenére a napi gyakorlatban továbbra is csak a HLA-fenotipizálás eredményét használják fel. Időközben a betegségek manifesztációjában egyre több ismeret áll a kutatók rendelkezésére az epigenetikai tényezők szerepéről. Coeliakiában mind a genetika, mind az epigenetika területén még számos kérdés megválaszolatlan. Ezen összefoglaló a jelenlegi ismeretekről kíván keresztmetszeti képet adni, különös tekintettel azok jövőbeni klinikai … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Histones are crucial in suppressing or inducing gene expression. They are cross-linked by transglutaminase, and epigenetics is important in CD pathophysiology [73][74][75][76]. Being a substrate of mTG, histone cross-linking might reduce its availability.…”
Section: Enhancing Intestinal Permeabilitymentioning
confidence: 99%
“…Histones are crucial in suppressing or inducing gene expression. They are cross-linked by transglutaminase, and epigenetics is important in CD pathophysiology [73][74][75][76]. Being a substrate of mTG, histone cross-linking might reduce its availability.…”
Section: Enhancing Intestinal Permeabilitymentioning
confidence: 99%
“…Many scientific studies have demonstrated that CD is a disease that involves various epigenetic mechanisms as well as it's genetic aspects. [2][3][4] Currently, a life-long gluten-free diet is an effective and available treatment option for patients with celiac disease. But, the widespread use of wheat-derived gluten in the food industry limits the effectiveness of life-long gluten diet [5].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the prolamin proteins -present in wheat, rye and barley -may contain immunogenic epitopes causing adverse symptoms of CD through the induction of inflammatory responses of the intestinal mucosa which lead to villous atrophy and malabsorption [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…More than 90% of CD patients express the antigen-presenting molecules human leukocyte antigen (HLA)-DQ-2/2.2/8, however only in a part of HLA-DQ-2/2.2/8 positive individuals develops CD (40% of the population carries these haplotypes without any evidence of CD) [6]. Based on recent epidemiological studies, similarly to other immunemediated diseases (allergy or asthma) CD may appear at any age and its prevalence is continuously increasing [1].…”
Section: Introductionmentioning
confidence: 99%